Comparative study of electrocardiogram signals acquired from different smart textile shirts - Mohd Nawawi, Muhammad Muizz; Sidek, Khairul Azami; Azman, Amelia Wong (IEEE, 2021)
Electrocardiogram (ECG) wearable smart textile has received a lot of attention due to its high flexibility, reusability, comfort, and ability to be used for home-based, real-life activities and real-time data acquisition. ECG wearable smart textile is a shirt with an embedded textile sensor that can capture ECG data in more convenient and user-friendly ways, particularly for continuous and long-term ECG data acquisition outside of the laboratory and clinical environment. However, the current challenge with wearable ECG smart textile is wearable smart textile data quality and reliability. Eight healthy volunteers participated in this study, whereas four wore the Hexoskin smart textile and four wear the HeartIn smart textile for the heart rate and ECG data acquisition. The study concludes that both wearable smart textiles, even though in different materials and different types of textile ECG electrodes, are suitable for ECG biometrics on-the-go. Although, both wearable smart textile data acquisition is affected by its wearer’s motion artefacts, concerning the shifting of body postures and the wearer body’s physical states. However, the heart rate and ECG morphology have yielded a promising results in real life and as on-the-go ECG biometric readiness.